2021
DOI: 10.1186/s13750-021-00246-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of artificial light on bird movement and distribution: a systematic map

Abstract: Background Artificial light is ubiquitous in the built environment with many known or suspected impacts on birds. Birds flying at night are known to aggregate around artificial light and collide with illuminated objects, which may result from attraction and/or disorientation. In other contexts, birds are repelled by light-based deterrents, including lasers and spotlights. Artificial light can also change birds’ perceptions of habitat quality, resulting in selection or avoidance of illuminated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 140 publications
0
10
0
Order By: Relevance
“…First, species that migrate at night are exposed to greater excess human density. Nocturnally migrating species are known to be disoriented by artificial light at night (Gauthreaux & Belser 2006;Adams et al 2021), which may lead birds to spend more time in human-modified areas. During overcast conditions, some birds may also use artificial light to navigate (Weisshaupt et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, species that migrate at night are exposed to greater excess human density. Nocturnally migrating species are known to be disoriented by artificial light at night (Gauthreaux & Belser 2006;Adams et al 2021), which may lead birds to spend more time in human-modified areas. During overcast conditions, some birds may also use artificial light to navigate (Weisshaupt et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As predictors, we considered several traits related to migration biology: the Julian date when the species starts its northward migration within North America, the overall distance the species migrates, and the time of day (nocturnal or diurnal) when its migration flight primarily occurs (Gauthreaux & Belser 2006;Van Doren et al 2017;McLaren et al 2018;Adams et al 2021).…”
Section: Comparative Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…One good quality, recent systematic map of the English literature (Adams et al, 2021) found 88 papers on using light to deter birds.…”
Section: Site Comparison*mentioning
confidence: 99%